Sibling recurrence risk in Dupuytren's disease. - Capstick, R; Bragg, T; Giele, H; Furniss, D (2013)
Dupuytren's disease is a complex condition, with both genetic and environmental factors contributing to its aetiology. We aimed to quantify the extent to which genetic factors predispose to the disease, through the calculation of sibling recurrence risk (ls), and to calculate the proportion of heritability accounted for by currently known genetic loci. From 174 siblings of patients with surgically confirmed disease, 100 were randomly selected. Controls were recruited from patients attending an ophthalmology outpatient clinic for eye conditions unrelated to diabetes. There were no statistically significant differences in baseline characteristics between the case and control groups. In siblings, 47% had Dupuytren's disease, compared with 10% of controls, giving a ls of 4.5. Currently known loci that predispose to Dupuytren's disease account for 12.1% of the total heritability of the disease. Dupuytren's disease was significantly more common in siblings than in controls. These results accurately quantify the magnitude of the genetic predisposition to Dupuytren's disease.